Of Humans, Pigs, and Souls An Essay on the Yagwoia Womba Complex - Mimica, Jadran (HAU Books, 2020)
For the Yagwoia-Angan people of Papua New Guinea womba is a malignant power with the potential to afflict any soul with cravings for pig meat and human flesh. Drawing on long-term research among the Yagwoia, and in an analysis informed by phenomenology and psychoanalysis, Jadran Mimica explores the womba complex in its local cultural-existential determinations and regional permutations. He attends to the lived experience of this complex in relation to the wider context of mortuary practices, feasting, historical cannibalism, and sorcery. His account of womba illuminates the moral meanings of Yagwoia selfhood, and associated senses of subjectivity and agency. Mimica concludes by reflecting on the recent escalation of concerns with witchcraft and sorcery in Papua New Guinea, specifically in relation to a new wave of Christian evangelism occurring in partnership with the state.